Haspin regulates Ras localization to promote Cdc24-driven mitotic depolarization - Quadri, Roberto (Cell Discov, 2020)
Cell polarization is of paramount importance for proliferation, differentiation, development, and it is altered during carcinogenesis. Polarization is a reversible process controlled by positive and negative feedback loops. How polarized factors are redistributed is not fully understood and is the focus of this work. In Saccharomyces cerevisiae, mutants defective in haspin kinase exhibit stably polarized landmarks and are sensitive to mitotic delays. Here, we report a new critical role for haspin in polarisome dispersion; failure to redistribute polarity factors, in turn, leads to nuclear segregation defects and cell lethality. We identified a mitotic role for GTP-Ras in regulating the local activation of the Cdc42 GTPase, resulting in its dispersal from the bud tip to a homogeneous distribution over the plasma membrane. GTP-Ras2 physically interacts with Cdc24 regulateing its mitotic distribution. Haspin is shown to promote a mitotic shift from a bud tip-favored to a homogenous PM fusion of Ras-containing vesicles. In absence of haspin, active Ras is not redistributed from the bud tip; Cdc24 remains hyperpolarized promoting the activity of Cdc42 at the bud tip, and the polarisome fails to disperse leading to erroneously positioned mitotic spindle, defective nuclear segregation, and cell death after mitotic delays. These findings describe new functions for key factors that modulate cell polarization and mitotic events, critical processes involved in development and tumorigenesis.